2023
DOI: 10.1038/s41598-023-37645-5
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of anti-plaque and remineralization efficacy of sugarless probiotic jelly candy supplemented with natural nano prebiotic additive

Abstract: We evaluated the anti-cariogenic effect of an experimental synbiotic compound containing probiotic Lacticaseibacillus rhamnosus (NRRL B-442)-based jelly candy supplemented with natural prebiotic grape seed extract (GSE) in a nanoemulsion formula on the colonization and establishment of Streptococcus mutans (ATCC 25175) and Actinomyces viscosus (ATTCC 19246) biofilms through counting colony forming units, scanning electron microscopy (SEM), and transmission electron microscopy (TEM). We were then analysing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Bias evaluation was performed according to the parameters established in Table 2 . The main risk of bias was found in that study limitations were either not reported in the study report [ 24 26 , 29 , 36 , 37 , 39 , 41 43 ] or were described briefly [ 27 , 28 , 31 34 , 40 , 44 ]. Secondly, there was a failure to include relevant ethical aspects such as institutional ethics committee approval, or patient informed consent for saliva sample collection was not clearly detailed in the article text, or a declaration of project financing and conflict of interest was absent [ 27 – 29 , 31 37 , 39 42 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bias evaluation was performed according to the parameters established in Table 2 . The main risk of bias was found in that study limitations were either not reported in the study report [ 24 26 , 29 , 36 , 37 , 39 , 41 43 ] or were described briefly [ 27 , 28 , 31 34 , 40 , 44 ]. Secondly, there was a failure to include relevant ethical aspects such as institutional ethics committee approval, or patient informed consent for saliva sample collection was not clearly detailed in the article text, or a declaration of project financing and conflict of interest was absent [ 27 – 29 , 31 37 , 39 42 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, three were conducted in Japan [ 24 , 36 , 42 ], seven in the United States [ 25 , 28 , 32 , 33 , 35 , 37 , 39 ], three in India [ 26 , 27 , 29 ], two in Australia [ 7 , 38 ] one in Saudi Arabia [ 30 ], one in Italy [ 31 ], one in France [ 34 ], one in Israel [ 40 ], one in England [ 41 ], one in Poland [ 43 ], and one in Egypt [ 44 ] sixteen were conducted at universities [ 7 , 24 26 , 28 , 30 35 , 37 41 ], and six in other types of institutions [ 27 , 29 , 36 , 42 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations